A hardware implementation of pulse coupled neural network (PCNN) for image feature extraction - Nguyễn Ngọc Hùng,; Hoàng Trọng Thức,; Bùi Trọng Tú, (Journal of Technical Education Science, 2012)
Couple Pulse Neural Network (PCNN) is the artificial neural network model was invented based on the visual cortex model of animals. Compared with other traditional processing methods, PCNN has some advantages such as not require training data, invariant to geometrical transformations of an image, robust against noise, highly stable structure. In this paper, the authors present results of a research on PCNN model and its applications in image feature extraction and image recognition. The proposed PCNN model is verified by the simulation results obtained from both Matlab software and FPGA implemetation. The demonstration is an image feature extraction block whose output is a feature vector of the input image. The mean square error (MSE) between the feature vector of the input image and standard feature vector is used as the criteria to recognize, classify the image. Images are used for this study are gray level ones. Experimental results show good agreements between Matlab software implementation and hardware implementation.